A+ guide to managing & maintaining your PC with Lab Exercises : hardware - Andrews, Jean; Verge, Todd (Australia : Cengage Learning Asia Pte Ltd, 2011)
The Lab Manual for A+ Guide to Managing and Maintaining Your PC, Sixth Edition is designed to accompany the A+ Guide to Managing and Maintaining Your PC, Sixth Edition. This lab manual provides the additional hands-on practice needed to succeed in the industry and serves as an excellent resource to prepare for CompTIA's A+ 2006 Exams.
Lab Exercises 1: Introducing Hardware -- Lab Exercises 2: Introducing Operating Systems -- Lab Exercises 3: PC Repairs Fundamentals -- Lab Exercises 4: Forms Factors and Power Supplies -- Lab Exercises 5: Processors and Chipsets -- Lab Exercises 6: Motherboards -- Lab Exercises 7: Upgrading Memory -- Lab Exercises 8: Hard Drives -- Lab Exercises 9: Installing and Supporting I/O Devices.
Keywords: COMPUTER SCIENCE -- EXAMINATIONS, QUESTIONS, ETC